PROTOCOL: Adult/child ratio and group size in early childhood education or care to promote the development of children aged 0–5 years: A systematic review. Issue 1 (25th February 2020) - Dalgaard, Nina T.; Bondebjerg, Anja; Klokker, Rasmus; Viinholt, Bjørn C. A.; Dietrichson, Jens
Abstract: This is the protocol for a Campbell review. The objectives are as follows: To synthesize data from studies to assess the impact of adult/child ratio and group size in ECEC on measures of process characteristics of quality of care and on child outcome measures.